2014
DOI: 10.1089/sur.2013.174
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Site Infection in Surgery for Benign Prostatic Hyperplasia: Comparison of Two Skin Antiseptics and Risk Factors

Abstract: In a cohort of patients submitted to open prostatectomy, SSI was not related to the type of antiseptic. The main risk factor was the presence of a urinary catheter preoperatively. All microorganisms isolated from the SSIs were characteristic of urinary tract infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…6,[25][26][27][28][29][30][31][32][33][34][35][36] In our study, there was a low incidence of contact dermatitis, and no significant difference between groups, consistent with sim ilarly low incidences (0% to 0.8%) reported in the literature. 6,29,34 Staphylococcus aureus was the primary organism cultured from wound swabs, again consistent with previous studies.…”
Section: Discussionsupporting
confidence: 86%
“…6,[25][26][27][28][29][30][31][32][33][34][35][36] In our study, there was a low incidence of contact dermatitis, and no significant difference between groups, consistent with sim ilarly low incidences (0% to 0.8%) reported in the literature. 6,29,34 Staphylococcus aureus was the primary organism cultured from wound swabs, again consistent with previous studies.…”
Section: Discussionsupporting
confidence: 86%
“…The essential procedures on these organs require the use of probes and drain, which are foreign bodies constituting a risk factor in the occurrence of SSI. Abreu D. et al [15], in a series of 70 patients undergoing prostatic adenomectomy, surgical site infections were noted in 18% of cases. Surgery on the urinary tract, especially when urine was infected, was a risk factor for surgical site infections.…”
Section: Discussionmentioning
confidence: 94%
“…This is because investigators in the past have reported contradictory results concerning the relationship between increasing age and risk of SSI12. Some researchers affirm that increasing age is associated with a greater risk of SSI13 while others believe factors indirectly related to age such as an increased prevalence of co-morbid conditions, increased severity of acute illness and decreased host response to bacterial invasion are the real reasons why older patients appear to have an increased risk of SSI14. A cohort by Kaye et al12 involving 144,485 consecutive surgical patients and 72,139 procedures however concluded that increasing age independently predicted an increased risk of SSI only until age 65 years; while after 65 years, increasing age independently predicted a decreased risk of SSI.…”
Section: Discussionmentioning
confidence: 99%